Seismic failure of multi-span simply supported RC slab-on-grider bridge in 2008 Wenchuan earthquake: Case study. (January 2019) - Hu, Menghan; Han, Qiang; Wen, Jianian; Bai, Yulei
Abstract: Multi-scale finite element (FE) modeling is an effective method to balance the computational efficiency and accuracy using different elements to simulate different parts of structures considering the demands of engineering practice. In order to analyze the earthquake-induced damage and collapse of Gaoyuan bridge in Wenchuan earthquake, the simplified rigid surface coupling method is developed to achieve the coupling between solid element and beam element based on LS-DYNA program at this study. The numerical results have shown that the failure of A2 abutment and strong pounding force cause the bridge superstructure lost longitudinal constraints, and the girders of the third span and forth span fell down due to oversize longitudinal displacement. Obviously, the multi-scale FE modeling is a high-efficiently analytical method for simulating local damage and even collapse of bridges structures under strong earthquake excitations. The inclined degree of bridge bents and the damage of concrete in different bridge piers using the multi-scale FE modeling method improved in this paper agrees well with actual earthquake damage of Gaoyuan highway bridge. Highlights: Simplified coupling method of rigid surface and the formula of displacement coordination were developed. Collapse modes and local damage mechanisms of Gaoyuan bridge collapsed during the Wenchuan earthquake were simulated. Compared results of numerical simulation with the actual collapse process in global level and damage details.